CORPORATIZATION OF RAILWAY INFRASTRUCTURE IN UKRAINE, POLAND, AND KAZAKHSTAN: A COMPARATIVE ANALYSIS OF MODELS AND OUTCOMES - Igor Dunayev; Serhii Hromov (Соціальна економіка)
This paper presents a comparative analysis of the models and outcomes of railway infrastructure corporatization in Ukraine, Poland, and Kazakhstan. The article aims to identify the key success factors, challenges, and opportunities for adapting the best practices of railway reform to the Ukrainian context. This goal is achieved through several research tasks: summarizing the historical context and evolution of railway corporatization in Ukraine; reviewing the initial conditions and main stages of railway corporatization in Poland and Kazakhstan; conducting a cross-comparative analysis of key indicators and reform outcomes; identifying lessons and recommendations for Ukraine based on the experiences of Poland and Kazakhstan; and developing proposals for applying successful foreign experiences to reform Ukraine’s railway system and foster national economic development. The research is based on a combination of historical and comparative methods. The authors provide a retrospective analysis of the corporatization process of JSC "Ukrzaliznytsia," identifying its main stages and outcomes. Through examples from Poland and Kazakhstan, alternative models of railway sector reform are analysed, considering both Eurointegration and Eurasian geopolitical contexts. Comparing the dynamics of key operational and financial indicators of railway companies in the three countries allowed for an assessment of the effectiveness of different approaches to corporatization. The article argues that successful reform of JSC "Ukrzaliznytsia" in the context of post-war recovery is critically dependent on creatively adapting Polish and Kazakh experiences, integrating them with Ukrainian realities. Three strategic priorities are proposed: optimizing the railway network for new logistics flows; digital transformation and process automation; and expanding public-private partnerships and cooperation with European railways. Key steps for implementation and ways to address challenges related to investment shortages and workforce deficits are outlined. The approaches and recommendations presented in the article may be useful for the management of JSC "Ukrzaliznytsia," government officials, experts, and all stakeholders involved in the development and implementation of Ukraine’s post-war railway sector recovery strategy.